Comparison of methods to classify ADRD in claims and cancer registry data. (17th December 2021) - Nalawade, Vinit; Murphy, James; Schempp, Tim; Yakuta, Melissa; Moore, Alison; Gilbert, Paul; Schiaffino, Melody
Abstract: Alzheimer's disease and related dementias(ADRD) affects 10.3% of older Americans (65+), among these 15-30% go on to be diagnosed with cancer. The highest burden of ADRD is experienced by Latino/a (12.2%) and African-American (13.8%) older adults. Older patients with pre-existing ADRD are less likely to receive guideline-concordant cancer care due to lack of consideration of cognitive status, and underestimation of ADRD diagnosis is an issue in secondary data. Our study compares two validated algorithms for classifying ADRD in a sample of cancer patients, the NCI-Charlson and CMS-Chronic Conditions Warehouse (CCW) index. We used existing claims from NCI's SEER-Medicare linked database (2004-2013, N=37, 932). Patients were selected based on cancer diagnosis at any stage with at least 36 months of data prior to diagnosis to identify ADRD. We analyzed breast, lung, prostate, cervix, head & neck(HNC), and colorectal(CRC) cancers(CA). We found a prevalence of 2.8% (9549 cases of ADRD+CA) using the NCI-index compared with a prevalence of 5.6% (18989 cases) with the CCW-index. ADRD+CA numbers differed significantly in all cancers for all races, however, we observed the greatest magnitude of difference among Latino/a and African-American patients. The NCI index significantly underestimated prevalence compared with the CCW: 1.21% vs 3.28% Breast; 2.29% vs 4.60% CRC; 2.88% vs 6.44% Lung; 1.36% vs 8.62% Prostate, and 4.21% vs 11.61% HNC. Our findings suggest a need to develop validated algorithms for classification, using an evidence-base generated by incorporating information and decision-making theories from the expertise of clinicians currently diagnosing ADRD using clinical assessments in diverse populations.